2022
DOI: 10.21203/rs.3.rs-1329015/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Xylotrechus smei (Cerambycidae: Cerambycinae: Clytini): A potential threat to Red Sanders cultivation

Abstract: Red sanders (Pterocarpus santalinus L.f.) is an economically important, endangered timber species endemic to the restricted forest tracts of the Eastern Ghats, India. Here, we report the occurrence of long horned beetle Xylotrechus smei infestation on red sanders for the first time from Telangana, India. Infestation was characterized by complete drying of standing trees, presence of galleries and bore holes in cut stems. In addition, supplementary description of X. smei, including the terminal abdominal segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The Buchanania latifolia was one of the important species in the forest 24 . A similar study done by several authors also found that, Shorea robusta, Terminalia alata, Lagerstroemia parviflora are the associate species of Buchanania latifolia [25][26][27] .…”
Section: Discussionmentioning
confidence: 70%
“…The Buchanania latifolia was one of the important species in the forest 24 . A similar study done by several authors also found that, Shorea robusta, Terminalia alata, Lagerstroemia parviflora are the associate species of Buchanania latifolia [25][26][27] .…”
Section: Discussionmentioning
confidence: 70%